A modified polyaspartic acid ester polyurea waterproof coating and preparation method thereof
By mixing the composite polyaspartate polyurea coating with the fluoride silicone polymer, the modified polyaspartate polyurea waterproof coating is solved, and the problem of insufficient wear resistance, chemical resistance and environmental adaptability of polyaspartate waterproof coating in certain application environments is achieved, and the performance improvement of the coating is achieved.
Patent Information
- Application Number
- CN202411217158.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-30
AI Technical Summary
Polyaspartate waterproof coatings have problems with insufficient wear resistance, chemical resistance and environmental adaptability in certain application environments.
Modified polyaspartate polyurea waterproof coating is formed by mixing the composite polyaspartate polyurea coating with the fluoride silicone polymer. The coating contains polyasparticle resin, nanofillers, flame retardants, pigments and other components, and improves the performance of the coating through specific formulations and construction processes.
Modified coatings have excellent performance in hardness, wear resistance, adhesion and high temperature resistance. They can maintain stable performance in complex environments, improving the environmental adaptability of the coatings.
Smart Images

Figure BDA0005021865240000051 
Figure BDA0005021865240000061 
Figure BDA0005021865240000062
Abstract
Description
Technical Field
[0001] The invention relates to the field of building waterproof materials, and in particular to a modified polyaspartic acid ester polyurea waterproof coating and a preparation method thereof. Background Art
[0002] The development of building waterproof materials can be traced back to ancient times, when people used natural materials such as asphalt and clay for waterproofing. With the advancement of science and technology, modern building waterproof materials have gradually diversified. From traditional asphalt membranes and waterproof coatings to polymer waterproof membranes and new waterproof coatings, every technological innovation has brought new solutions to building waterproof projects.
[0003] Early asphalt membranes had a certain waterproof effect, but there were problems such as difficulty in construction and poor durability. The subsequent polymer waterproof membranes have significantly improved in performance, but they have high requirements for construction conditions and have limitations in the treatment of some special parts. The development of waterproof coatings has undergone a transition from solvent-based to water-based, and from low performance to high performance. Solvent-based waterproof coatings contain a large amount of organic solvents, which have a great impact on the environment and the health of construction workers, and have gradually been replaced by water-based coatings. Water-based waterproof coatings have greatly improved in environmental performance, but there is still room for improvement in waterproof performance and durability.
[0004] The rapid development of the construction industry has put forward higher and higher requirements on the performance of waterproof materials. Among the many waterproof materials, coating products have been widely used in the field of building waterproofing due to their convenient construction and strong adaptability. Among them, polyaspartic acid ester waterproof coating, as a new type of high-performance coating, has excellent performance in waterproofing, but there are still some problems that need to be improved in the face of complex and changing application environments.
[0005] In some areas that are frequently subjected to friction, such as underground parking lots and industrial plant floors, the wear resistance of polyaspartic acid waterproof coatings is difficult to meet the requirements. Long-term friction may cause the waterproof layer to become thinner and damaged, thus affecting the waterproof effect. In working environments such as chemical plants and sewage treatment plants, buildings are often exposed to various chemicals such as acids, alkalis, and salts. When polyaspartic acid waterproof coatings are exposed to these highly corrosive chemicals, chemical reactions may occur, resulting in a decrease in the performance of the waterproof layer. Under extreme temperature and humidity conditions, the performance of polyaspartic acid waterproof coatings may also deteriorate to a certain extent. For example, in a high temperature and high humidity environment, the coating may experience problems such as blistering and softening; in a low temperature and dry environment, the coating may become brittle and prone to cracking.
[0006] In order to solve the problems of polyaspartic acid waterproof coatings, some measures have been taken, such as adding wear-resistant additives and enhancing the chemical corrosion resistance of coatings, but these methods still have certain limitations. Although the addition of wear-resistant additives can improve the wear resistance of coatings to a certain extent, it may affect other properties of coatings, such as flexibility and adhesion. Moreover, the selection and addition amount of wear-resistant additives need to be precisely controlled, otherwise the desired effect may not be achieved. Chemical resistance improvement can be achieved by adding chemically resistant components (such as fluorocarbon resins, epoxy resins, etc.) to the coating. However, the addition of these components may increase the cost of the coating and may also affect the construction performance and curing speed of the coating. In terms of environmental adaptability optimization, the mechanical properties of the coating in extreme environments can be improved by adjusting the formulation and construction process of the coating. However, this method often requires a lot of testing and optimization work, and the effect may not be stable. In view of the above problems existing in the application of polyaspartic acid waterproof coatings, research is mainly conducted on the formulation optimization of new waterproof coatings, the synergistic effect of each component, and the improvement of construction technology.
[0007] In view of the problems existing in the prior art, how to provide a new type of polyaspartic acid ester waterproof coating to solve the problem that although the polyaspartic acid ester waterproof coating on the market has good waterproof performance, it still has insufficient wear resistance, chemical resistance and environmental adaptability in certain application environments is a problem to be urgently solved by the present invention. Summary of the invention
[0008] Purpose of the invention:
[0009] The object of the present invention is to provide a modified polyaspartic acid ester polyurea waterproof coating to solve the problem of how to make the coating have high hardness, good wear resistance, adhesion and high temperature resistance proposed in the above background technology.
[0010] The technical solution of the present invention:
[0011] A modified polyaspartic acid ester polyurea waterproof coating, characterized in that the coating is mixed with a composite polyaspartic acid ester polyurea coating and a fluorinated siloxane polymer; wherein:
[0012] The composite polyaspartic acid ester polyurea coating comprises polyaspartic acid ester resin, nano filler, flame retardant, pigment, dispersant, defoamer, leveling agent and plasticizer;
[0013] The fluorinated siloxane polymer is obtained by polymerization of tetrafluoroethylene and tetrakis(trimethylsiloxy)silane;
[0014] Furthermore, the raw materials of the composite polyaspartic acid ester polyurea coating are 100% by mass, including: 30-60% polyaspartic acid ester resin, 0.5-2% nano filler, 0.1-1% flame retardant, 10-15% pigment, 0.5%-2% dispersant, 0.5%-2% defoamer, 0.5%-2% leveling agent, 1%-5% plasticizer, and the balance is water.
[0015] Furthermore, the polyaspartic acid ester resin model is a mixture of one or more of F330, F420, and F520.
[0016] Furthermore, the nano filler is a mixture of one or more of nano silicon dioxide, nano titanium dioxide and nano calcium carbonate.
[0017] Furthermore, the flame retardant is a mixture of one or more of nano magnesium hydroxide and nano aluminum hydroxide.
[0018] The preparation method of the fluorinated siloxane polymer comprises the following steps:
[0019] S1: prepare tetrafluoroethylene and tetrakis(trimethylsiloxy)silane for use, dry the reaction vessel and replace with nitrogen to exclude air and moisture;
[0020] S2: Add the tetrakis(trimethylsiloxy)silane weighed in step S1 into the reaction vessel, then add hydrogen peroxide, and then add tetrafluoroethylene, and control the pressure to 15-25 kgf / cm 2 , raising the temperature of the reaction system to 60-80° C., and polymerizing for 4-6 hours to generate a polymer;
[0021] S3: separating, purifying and drying the polymerized product to obtain a fluorinated siloxane polymer.
[0022] Furthermore, the mass ratio of tetrafluoroethylene to tetrakis(trimethylsiloxy)silane is 10-15:1.
[0023] Furthermore, the mass ratio of the composite polyaspartic acid ester polyurea coating to the fluorinated silicone polymer is 8 to 10:1.
[0024] The preparation method of the composite polyaspartic acid ester polyurea coating comprises the following steps:
[0025] S1: Weigh polyaspartic acid ester resin, nanofiller, flame retardant, pigment, dispersant, defoamer, leveling agent and plasticizer for later use;
[0026] S2: Put polyaspartic acid ester resin, pigment, dispersant, defoamer, leveling agent and plasticizer into a stirrer and stir evenly;
[0027] S3: In step S2, the nanofiller and the flame retardant are gradually added into the stirrer, the temperature is raised to 150-180° C., and the mixture is stirred for reaction for 1-2 hours;
[0028] S4: After the reaction is completed, the mixed coating is filtered using a filter to remove impurities and insoluble particles therein, thereby obtaining the composite polyaspartic acid ester polyurea coating.
[0029] Furthermore, the pigment is titanium dioxide.
[0030] Furthermore, the dispersant is dispersant 5040.
[0031] Furthermore, the defoaming agent is KP-341 defoaming agent produced by Shin-Etsu of Japan.
[0032] Furthermore, the leveling agent is KP-324 leveling agent produced by Shin-Etsu of Japan.
[0033] Furthermore, the plasticizer is diethyl phthalate.
[0034] The present application also provides a method for preparing a modified polyaspartic acid ester polyurea waterproof coating, which is characterized by comprising the following steps:
[0035] The composite polyaspartic acid ester polyurea coating and the fluorinated siloxane polymer are mixed according to a mass ratio, heated to 120-150° C., and stirred for 1-2 hours to obtain the modified polyaspartic acid ester polyurea waterproof coating.
[0036] Fluorinated siloxane polymer improves tensile strength: the molecular structure of fluorinated siloxane has strong bond energy and rigidity, which can enhance the cohesion and intermolecular force of the coating, thereby improving the tensile strength; enhance wear resistance: its low surface energy and good lubricity can reduce the friction coefficient, reduce wear, and improve the wear resistance of the coating; improve chemical corrosion resistance: fluorinated groups are inert to many chemicals, can effectively block the erosion of chemicals, and enhance the chemical corrosion resistance of the coating; improve environmental adaptability: excellent weather resistance and hydrophobicity and oleophobicity enable it to maintain stable performance under different environmental conditions, improving the environmental adaptability of the coating. Polyaspartic acid ester resin has a unique molecular structure that can form a cross-linked network, enhance the cohesion of the coating, thereby helping to improve tensile strength and wear resistance. At the same time, the functional groups in the molecule can react less with chemicals, reducing the impact of chemical corrosion. Nanofillers can be evenly dispersed in the coating and form a good interface bonding with the resin matrix, effectively transferring stress, thereby enhancing tensile strength. They also play a reinforcing and supporting role, reducing material loss during wear and improving wear resistance. Nanofillers can fill tiny pores and defects in the coating, reduce the penetration channels of chemical substances, and enhance chemical corrosion resistance; nanofillers improve the thermal stability and physical structure stability of the coating, helping to adapt to different environmental conditions.
[0037] In summary, fluorinated silicone polymers, polyaspartic acid resins, and nanofillers synergistically improve the tensile strength, wear resistance, chemical corrosion resistance, and environmental adaptability of the coating through their respective properties and interactions.
[0038] Beneficial effects:
[0039] The present invention provides a modified polyaspartic acid ester polyurea waterproof coating and a preparation method thereof. The coating has strong environmental adaptability, excellent tensile strength, wear resistance, and chemical corrosion resistance, limits the elongation at break range, and controls or reduces the emission of harmful substances, and has broad application prospects. DETAILED DESCRIPTION
[0040] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following experimental examples are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0041] Unless otherwise specified, the chemical reagents used in the present invention are all commercially available analytically pure.
[0042] The polyaspartic acid ester resins used in the following experimental examples, models F330, F420, and F520, were purchased from Shenzhen Feiyang Junyan New Materials Co., Ltd.; the dispersant 5040 was purchased from Guangzhou Fufei Chemical Co., Ltd.
[0043] Preparation of Fluorinated Silicone Polymer A:
[0044] S1: prepare 10 g of tetrafluoroethylene and 1 g of tetrakis(trimethylsiloxy)silane for use, dry the reaction container and replace it with nitrogen to exclude air and moisture;
[0045] S2: Add the tetrakis(trimethylsiloxy)silane weighed in step S1 into the reaction vessel, then add 0.1 g of hydrogen peroxide, and then add the tetrafluoroethylene weighed in step S1, and control the pressure to 20 kgf / cm 2 , the reaction system was heated to 70°C and the polymerization reaction was carried out for 4 hours to generate a polymer;
[0046] S3: separating, purifying and drying the polymerized product to obtain fluorinated siloxane polymer A.
[0047] Preparation of Fluorinated Silicone Polymer B:
[0048] The difference between the present preparation and the fluorinated siloxane polymer A is that the 10 g of tetrafluoroethylene prepared in step S1 is replaced with 15 g of tetrafluoroethylene.
[0049] Preparation of Fluorinated Silicone Polymer C:
[0050] The difference between the present preparation and the fluorinated siloxane polymer A is that the 10 g of tetrafluoroethylene prepared in step S1 is replaced with 5 g of tetrafluoroethylene.
[0051] Preparation of Fluorinated Silicone Polymer D:
[0052] The difference between the present preparation and the fluorinated siloxane polymer A is that the 10 g of tetrafluoroethylene prepared in step S1 is replaced with 20 g of tetrafluoroethylene.
[0053] Preparation of composite polyaspartic acid ester polyurea coating:
[0054] S1: Weigh polyaspartic acid ester resin, nanofiller, flame retardant, pigment, dispersant, defoamer, leveling agent and plasticizer for later use;
[0055] S2: Put polyaspartic acid ester resin, pigment, dispersant, defoamer, leveling agent and plasticizer into a stirrer and stir evenly;
[0056] S3: In step S2, the nanofiller and the flame retardant are gradually added into the stirrer, the temperature is raised to 160° C., and the mixture is stirred for reaction for 2 hours;
[0057] S4: After the reaction is completed, the mixed coating is filtered using a filter to remove impurities and insoluble particles therein, thereby obtaining the composite polyaspartic acid ester polyurea coating.
[0058] Composite polyaspartic acid ester polyurea coating 1~7:
[0059] The composite polyaspartic acid ester polyurea coatings were prepared according to the above-mentioned preparation method. Table 1 is the ingredient list of composite polyaspartic acid ester polyurea coatings 1 to 7.
[0060] Table 1
[0061]
[0062]
[0063] Preparation of modified polyaspartic acid ester polyurea waterproof coating:
[0064] The composite polyaspartic acid ester polyurea coating and the fluorinated siloxane polymer are mixed according to a mass ratio, the temperature is raised to 120° C., and stirred for 1.5 hours to obtain the modified polyaspartic acid ester polyurea waterproof coating.
[0065] The modified polyaspartic acid ester polyurea waterproof coating was prepared according to the above preparation method. Table 2 is a composition table of the composite polyaspartic acid ester polyurea coatings 1 to 7 and fluorinated siloxane polymers A, B, C, and D.
[0066] Table 2
[0067]
[0068] Performance test: Before the preparation of the coating sample, the sample and the test equipment used should be placed under standard test conditions for at least 24 hours. Under standard test conditions, the required sample volume is weighed to ensure that the final coating thickness is about 1.5mm. After unpacking the placed sample, take a sample from the sample with qualified appearance and make a film directly without stirring. The film frame must not be warped and the surface must be smooth. To facilitate film removal, a film release agent can be used before film coating. The sample can be filmed once or twice according to its viscosity. The interval between the two times should not exceed 24 hours. When the film is formed twice, it is required to be dried before applying the next layer. The film should not be formed more than twice, and the surface should be scraped flat for the last time. The prepared coating is cured for 72 hours under standard test conditions, and then the film is removed. The coating is turned over and placed on a plate rack with mesh eyes for ventilation, and then cured for 96 hours under standard test conditions. Check the appearance of the coating and cut the test piece from the smooth and flat coating with no bubbles on the surface.
[0069] 1. Tensile strength
[0070] Prepare dumbbell type 1 according to GB / T528-2009 and conduct the test according to Chapter 9 of GB / T 16777-2008. The test speed is (500±50)mm / min.
[0071] 2. Wear resistance
[0072] The specimen was prepared into a size of Φ100mm and tested according to GB / T1768-2006. The CS-10 rubber grinding wheel was used for measurement.
[0073] 3. Chemical corrosion resistance
[0074] The specimens were prepared into a size of 100mm×25mm, and then subjected to acid treatment (10% hydrochloric acid), alkali treatment (10% sodium hydroxide), and salt treatment (saturated sodium chloride) to test low-temperature flexural properties. The low-temperature flexural properties were tested in accordance with 14.2.3 of GB / T16777-2008. The specimens were visually inspected for cracks.
[0075] 4. Low temperature elongation at break
[0076] According to GB / T528-2009, cut dumbbell type 2 specimens, put them into a low temperature tensile test chamber at -45℃, keep them at this temperature for 1h, and then directly test them in the low temperature tensile test chamber according to Chapter 9 of GB / T16777-2008. The test temperature is -45℃, the distance between the clamps is 30mm, and the test speed is (500±50)mm / min. The elongation at break is calculated by the displacement between the clamps. The test results are taken as the arithmetic mean of 5 specimens.
[0077] Table 3: Performance test results
[0078]
[0079] It can be seen from Table 3 that the modified polyaspartic acid ester polyurea waterproof coating of the present invention has good tensile strength, wear resistance, chemical corrosion resistance and environmental adaptability. Specifically, it can be seen from the comparison between Experimental Examples 3 to 4 and Experimental Example 2 that when preparing the fluorinated siloxane polymer, the unreasonable mass ratio of tetrafluoroethylene to tetrakis(trimethylsiloxy)silane will cause the prepared modified polyaspartic acid ester polyurea waterproof coating to have poor tensile strength, wear resistance and chemical corrosion resistance, and fail to meet the expected requirements; it can be seen from Experimental Examples 6 to 7 and Experimental Example 2 that when preparing the composite polyaspartic acid ester polyurea coating, the polyaspartic acid ester resin content is too high or too low, which will cause the prepared modified polyaspartic acid ester polyurea waterproof coating to have poor tensile strength, wear resistance and chemical corrosion resistance. Deteriorated and failed to meet the expected requirements; by comparing Experimental Example 8 with Experimental Example 2, it can be seen that when preparing the composite polyaspartic acid ester polyurea coating, not adding nanofillers will lead to the prepared modified polyaspartic acid ester polyurea waterproof coating having poor tensile strength and wear resistance, which will not meet the expected requirements; by comparing Experimental Examples 10 to 11 with Experimental Example 2, it can be seen that when preparing the modified polyaspartic acid ester polyurea waterproof coating, the unreasonable mass ratio of the fluorinated silicone polymer to the composite polyaspartic acid ester polyurea coating will lead to the prepared modified polyaspartic acid ester polyurea waterproof coating having poor tensile strength and wear resistance, which will not meet the expected requirements.
[0080] The present invention can also be implemented by various other experimental examples. Without departing from the spirit and essence of the present invention, technicians familiar with the field can make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A modified polyaspartic acid ester polyurea waterproof coating, characterized in that: The coating is prepared by mixing a composite polyaspartic acid ester polyurea coating and a fluorinated silicone polymer; wherein, The composite polyaspartic acid ester polyurea coating comprises polyaspartic acid ester resin, nano filler, flame retardant, pigment, dispersant, defoamer, leveling agent and plasticizer; The fluorinated siloxane polymer is obtained by polymerization of tetrafluoroethylene and tetrakis(trimethylsiloxy)silane; The raw materials of the composite polyaspartic acid ester polyurea coating are calculated as 100% by mass, including: 30-60% polyaspartic acid ester resin, 0.5-2% nano filler, 0.1-1% flame retardant, 10-15% pigment, 0.5%-2% dispersant, 0.5%-2% defoamer, 0.5%-2% leveling agent, 1%-5% plasticizer, and the balance is water; The preparation method of the fluorinated siloxane polymer comprises the following steps: S1: prepare tetrafluoroethylene and tetrakis(trimethylsiloxy)silane for use, dry the reaction vessel and replace with nitrogen to exclude air and moisture; S2: Add the tetra(trimethylsiloxy)silane weighed in step S1 into the reaction vessel, then add hydrogen peroxide, and then add tetrafluoroethylene, and control the pressure to 15~25kgf / cm 2 , raising the temperature of the reaction system to 60-80°C, and polymerizing for 4-6 hours to generate a polymer; S3: separating, purifying and drying the polymerized product to obtain a fluorinated siloxane polymer; The mass ratio of tetrafluoroethylene to tetrakis(trimethylsiloxy)silane is 10-15:1; The mass ratio of the composite polyaspartic acid ester polyurea coating to the fluorinated siloxane polymer is 8-10:
1.
2. A modified polyaspartic acid ester polyurea waterproof coating according to claim 1, characterized in that: The polyaspartic acid ester resin model is a mixture of one or more of F330, F420 and F520.
3. The modified polyaspartic acid ester polyurea waterproof coating according to claim 1, characterized in that: The nano filler is a mixture of one or more of nano silicon dioxide, nano titanium dioxide and nano calcium carbonate.
4. The modified polyaspartic acid ester polyurea waterproof coating according to claim 1, characterized in that: The flame retardant is a mixture of one or more of nano magnesium hydroxide and nano aluminum hydroxide.
5. The modified polyaspartic acid ester polyurea waterproof coating according to claim 1, characterized in that: The preparation method of the composite polyaspartic acid ester polyurea coating, The following steps are involved: S1: Weigh polyaspartic acid ester resin, nanofiller, flame retardant, pigment, dispersant, defoamer, leveling agent and plasticizer for later use; S2: Put polyaspartic acid ester resin, pigment, dispersant, defoamer, leveling agent and plasticizer into a stirrer and stir evenly; S3: In step S2, the nanofiller and the flame retardant are gradually added into the stirrer, the temperature is raised to 150-180° C., and the mixture is stirred for reaction for 1-2 hours; S4: After the reaction is completed, the mixed coating is filtered using a filter to remove impurities and insoluble particles therein, thereby obtaining the composite polyaspartic acid ester polyurea coating.
6. A method for preparing a modified polyaspartic acid ester polyurea waterproof coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: The composite polyaspartic acid ester polyurea coating and the fluorinated siloxane polymer are mixed according to a mass ratio, the temperature is raised to 120-150° C., and stirred for 1-2 hours to obtain the modified polyaspartic acid ester polyurea waterproof coating.
Citation Information
Patent Citations
Polyaspartic acid ester polyurea protective coating with enhanced mechanical properties as well as preparation method, use method and application thereof
CN109439160A
Polyaspartic acid ester polyurea protective paint with good corrosion resistance, preparation method, using method and application
CN109456684A